2020
DOI: 10.1002/adma.201903269
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Molecular White‐Light Emitters and Their Potential WOLED Applications

Abstract: White organic light‐emitting diodes (WOLEDs) are superior to traditional incandescent light bulbs and compact fluorescent lamps in terms of their merits in ensuring pure white‐light emission, low‐energy consumption, large‐area thin‐film fabrication, etc. Unfortunately, WOLEDs based on multilayered or multicomponent (red, green, and blue (RGB)) emissive layers can suffer from some remarkable disadvantages, such as intricate device fabrication and voltage‐dependent emission color, etc. Single molecules, which ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
167
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(176 citation statements)
references
References 190 publications
(427 reference statements)
1
167
0
Order By: Relevance
“…It is suggested that the emission originates from the π-π stacking system induced aggregation, and ClCbz has a relatively more effective donor-acceptor interaction than HCbz, MeCbz and SCbz in solid state (ESI). [19] The calculation results further support this suggestion (ESI). Quantum yields of all HCbz derivatives in the solid states were smaller than the values in THF, respectively.…”
Section: Scheme 4 the Suggested Two-step Reaction Pathway For Radicalsupporting
confidence: 55%
“…It is suggested that the emission originates from the π-π stacking system induced aggregation, and ClCbz has a relatively more effective donor-acceptor interaction than HCbz, MeCbz and SCbz in solid state (ESI). [19] The calculation results further support this suggestion (ESI). Quantum yields of all HCbz derivatives in the solid states were smaller than the values in THF, respectively.…”
Section: Scheme 4 the Suggested Two-step Reaction Pathway For Radicalsupporting
confidence: 55%
“…[77][78][79][80][81][82] So far, many commercialized emitters are based on these phosphors (such as iridium(III) complex). [83][84][85][86][87][88] However, these noble metals often have some disadvantages (such as high cost and low abundance in nature). The exploration of low-cost, relatively abundant, and less-toxic phosphorescent manganese(II) complexes could be the key to solve this problem.…”
Section: Organic Light-emitting Diodesmentioning
confidence: 99%
“…[ 21 ] However, the luminescent color are environmentally sensitive, and could response to various external stimuli, [ 30 ] inferring vulnerable interact‐force system between molecules. Consequently, although highly reproducible white emission can be achieved in single‐doped PhOLEDs by confining the monomeric and excimeric emission, [ 31,32 ] the precisely tuned emission might have unexpected color shifting under current change. [ 17,33 ] Nonetheless, in spite of great importance for practical application.…”
Section: Figurementioning
confidence: 99%